2023
DOI: 10.3390/nu15092115
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Alleviates Diabetic Periodontitis-Induced Alveolar Osteocyte Ferroptosis Possibly via Regulation of SLC7A11/GPX4

Abstract: The mode and mechanism of diabetic periodontitis-induced alveolar-osteocyte death are still unclear. This study aimed to investigate the occurrence of ferroptosis in alveolar osteocytes during diabetic periodontitis and the therapeutic potential of resveratrol to alleviate osteocyte ferroptosis. Diabetic periodontitis was induced in C57/BL6-male mice and treated with or without resveratrol. Periodontitis pathogenicity was analyzed by micro-CT and histology, and alveolar-osteocyte ferroptosis was analyzed by im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…It is defined by the body’s incapacity to regulate normal blood sugar levels, stemming from either insulin resistance or insufficient insulin production. Additionally, diabetes can contribute to the development of other conditions, such as diabetic nephropathy, cardiomyopathy, and neuropathies [ 77 , 78 , 79 ]. Interestingly, polyphenols quercetin, rhein, and glabridin have been shown to attenuate diabetic nephropathy through inhibition of ferroptosis.…”
Section: Resultsmentioning
confidence: 99%
“…It is defined by the body’s incapacity to regulate normal blood sugar levels, stemming from either insulin resistance or insufficient insulin production. Additionally, diabetes can contribute to the development of other conditions, such as diabetic nephropathy, cardiomyopathy, and neuropathies [ 77 , 78 , 79 ]. Interestingly, polyphenols quercetin, rhein, and glabridin have been shown to attenuate diabetic nephropathy through inhibition of ferroptosis.…”
Section: Resultsmentioning
confidence: 99%
“…The non-flavonoid polyphenolic compound Resveratrol (RES) was found to promote ferroptosis-mediated recovery of motor function in SCI mice by modulating the Nrf2/GPX4 pathway in an SCI model ( Ni et al, 2023 ). Meanwhile, RES protects human bronchial epithelial cells (BEAS-2B) from ferroptosis by acting on the ferroptosis pathway and inhibits diabetic periodontitis-induced ferroptosis in alveolar osteoblasts ( Li et al, 2023c ), which offers the possibility of disease treatment. Furthermore, Kosuke Kato et al showed that quercetin and RES inhibit ferroptosis by inhibiting iron-catalyzed hydroxyl radicals and are independent of the Nrf2-ARE pathway ( Kato et al, 2023 ).…”
Section: Small Molecule Ferroptosis Inhibitorsmentioning
confidence: 99%
“…Similarly, mitochondrial oxidative deregulation was proved to be a mutual systemic cytopathological feature of periodontitis and type 2 diabetes [17,18]. Moreover, there is evidence to suggest that the application of prominent polyphenolic compounds that optimize mitochondrial function, such as resveratrol, ameliorated the destruction of renal structures in mice with periodontitis [19] and alleviated the ferroptosis of alveolar osteocytes in mice with diabetic periodontitis [20]. In light of the mitochondrial pathway being so extensively involved in the pathological process of periodontitis, it has received mounting interest in exploring how the crucial periodontal pathogen, P. gingivalis, disrupts mitochondria.…”
Section: Introductionmentioning
confidence: 99%